Setting Adequate Wages for Workers: Managers' Work Experience, Incentive Scheme and Gender Matter - David Huber; Leonie Kühl; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2022)
Many societies report an increasingly divergent development of managers' salaries compared to that of their workforce. Moreover, there is often a lack in diversity amongst managerial boards. We investigate the role of managers' gender and incentive scheme on wages chosen for workers by conducting two experimental studies. The data reveal male managers respond in more self-oriented ways to their incentive scheme. Further, we find that experience with the workers' task can increase appreciation of workers. Effects are strongest when the managers' compensation scheme rules out self-orientation. Overall, female managers display more consistency in choosing adequate wages for workers, i.e. their choices are less affected by incentives. An increase in diversity may thus help reducing salary disparities and foster work atmosphere.
Keywords: D01; J16; 330; adequate wages; real work experiment; gender